1995
DOI: 10.1109/84.465122
|View full text |Cite
|
Sign up to set email alerts
|

Plasma planarization for sensor applications

Abstract: Abstract-Filling trenches in silicon using phosphosilicate glass (PSG) provides many possibilities for novel device structures for sensors and actuators. This paper describes a plasma planarization technique that provides fully planarized PSG filled silicon trenches for sensor applications. The technique consists of planarizing the substrate using two photoresist layers and plasma etching-back. The lower resist layer is the A25214 image reversal resist, which is patterned and then thermally cured. The upper re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Similarly, surface planarity and roughness are of crucial interest for optical MEMS devices. MEMS researchers have demonstrated success with local planarization techniques for some sensor applications [5,6]. The challenge in using CMP for MEMS is that structures with multiple structural levels often have several micrometers of built-up topography.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, surface planarity and roughness are of crucial interest for optical MEMS devices. MEMS researchers have demonstrated success with local planarization techniques for some sensor applications [5,6]. The challenge in using CMP for MEMS is that structures with multiple structural levels often have several micrometers of built-up topography.…”
Section: Introductionmentioning
confidence: 99%
“…To adopt this technique for the waveguides, for the unevenness of ∼5 μm, etching with two sacrificial layers is also reported. 25 Ruano et al 26 reported monolithic integration of waveguide and microfluidic system including microchannel and liquid reservoirs by depositing glass using flame hydrolysis deposition (FHD) and etching with deep reactive ion etching (DRIE), followed by sealing the device with the help of two PDMS layers. Herein, to get a hermetic sealing, a thin flexible PDMS layer is bonded between the nonplanar waveguide and a thick PDMS layer containing the fluidic ports.…”
Section: Silica-on-silicon Waveguidementioning
confidence: 99%
“…Some processes such as BPSG reflow, spin-onglass and plasma etching can only smooth over the local features and fail to deliver the desired planarity across the wafer. Li, et al , 6 proposed a plasma planarization method with two photoresist layers as a means to fabricate a planarized PSG trench in a silicon substrate. However, this method requires equal etching rates between the two photoresists and the PSG film and can, therefore, only be used in limited material sets.…”
Section: Introductionmentioning
confidence: 99%